Adobe Illustrator visual quickstart guide. (Peachpit Press, 2022)
Learn Adobe Illustrator with the Visual QuickStart Guide, the quick and easy way!Visual QuickStart Guide is an easy, visual approach to learning. Concise steps and explanations guide you through Adobe Illustrator, getting you up and running in no time. In addition, the free Web Edition of the book includes more than 40 videos, enhancing and expanding the information in the book while providing an alternative method for learning. Whether you're an experienced designer or an enthusiastic newcomer, Illustrator gives you all the tools you need to begin creating impressive vector artwork.